Features composites-odorativov in the monuments of the Ukrainian language of Article XI–XIII. (Philological Studies: Scientific Bulletin of Kryvyi Rih State Pedagogical University, 2015)
Study of the history of lexical structure of the Ukrainian language is impossible without finding out the history of individual groups, in particular, odorativov. Analysis of the composites-odorativov vocabulary is the smell in old Ukrainian period.
Keywords: сomposites; derivative; prefiksoid; odorativ; derivatives